An empirical investigation of critical success factors influencing the successful TQM implementation for firms with different strategic orientation. Issue 9 (2nd October 2017) - Kumar, Vimal; Sharma, R.R.K.
Abstract : Purpose: It has been found that critical success factors (CSFs) are responsible for successful implementation of total quality management (TQM) system. The purpose of this paper is to make a comparative analysis of the importance of 20 TQM CSFs to the strategic choices of the firms such as innovators, prospectors, and defenders. Design/methodology/approach: From extant literature review on TQM, 20 CSFs have been carried out. The empirical data for this study was drawn from a survey of 111 firms in India. One-way ANOVA approach has been applied for analysis. Findings: The findings of the research show that the CSFs hold importance for different firm's strategy. From these 20 CSFs, some CSFs may be critically important for all three types of firm, while others have their significant roles for innovators, prospectors, and defenders individually which are better prepared for TQM implementation. Practical implications: The results of this study present the importance of knowing the appropriate CSFs to a strategy of the firms. The emphasis on CSFs will help organizations in accepting and rejecting TQM practices when they try to implement TQM and it is equally important in a global context. Apparently, it is evident that if there is a mismatch of strategy and CSFs with TQM practices it may interrupt the smooth operations of the company. Originality/value: This research can be useful for those firms who are in the starting phase of TQM implementation with consideration of CSFs. Moreover, this research also attempts to inspire managers to consider the appropriate CSFs for implementing TQM effectively in their firms.